The pursuit of empowerment through pornography - Siti Adriana Zahirah Binte Zulkiffli (Nanyang Technological University, 2025)
The feminist debate on pornography is divided into two main perspectives: anti-pornography and pro-pornography feminism. Anti-pornography feminists argue that pornography is a male prerogative that oppresses women and other sexual minorities by sexually objectifying them to serve male desires. In contrast, pro-pornography feminists contend that pornography facilitates sexual freedom for women and sexual minorities, a fundamental step toward liberation. Thus, pornography can foster empowerment rather than oppression.